2003
DOI: 10.2135/cropsci2003.1441
|View full text |Cite
|
Sign up to set email alerts
|

Root Physiology of Less Fall Dormant, Winter Hardy Alfalfa Selections

Abstract: The physiological mechanisms causing fall dormancy (FD)‐induced differences in alfalfa (Medicago sativa L.) shoot growth in autumn and winter hardiness are not understood. The objective of this research was to examine root physiology of experimental germplasms selected for decreased FD that also were selected simultaneously for high winter hardiness. Dormant and semi‐dormant cultivars and germplasms had high root sugar concentrations that were positively associated with winter hardiness. Root amino N and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…This suggested that in winter types sugar production is elevated, providing a potential cryoprotectant and needed carbohydrate for basal metabolism and spring regrowth. In perennial alfalfa (Medicago sativa L.) winter hardiness is associated with increased sugar concentration in roots and crowns in the autumn acclimation period (Haagenson et al 2003). Protein levels may also increase (Cunningham et al 1998), but not in all cases (Weishaar et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggested that in winter types sugar production is elevated, providing a potential cryoprotectant and needed carbohydrate for basal metabolism and spring regrowth. In perennial alfalfa (Medicago sativa L.) winter hardiness is associated with increased sugar concentration in roots and crowns in the autumn acclimation period (Haagenson et al 2003). Protein levels may also increase (Cunningham et al 1998), but not in all cases (Weishaar et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This was necessary to prevent a skewing of the error variance derived in other environments. Of the 99 total experimental units analyzed over the three environments (Central Ferry and Pullman in 2002-2003, and Central Ferry 2003-2004 there were two missing values, each in a different replication. These were accession FO-4 at Central Ferry in 2002-2003and FO-2 at Pullman also in 2002-2003.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, WSC accumulation is considered a primary factor for cold tolerance and the taproot concentrations in late autumn have been positively correlated with enhanced alfalfa winter survival (McKenzie et al, 1988; Castonguay et al, 1995; Dhont et al, 2002). In addition, Haagenson et al (2003b) documented positive relationships between winter survival, WSC concentration in taproots, and FD rating of several alfalfa entries.…”
mentioning
confidence: 90%
“…However, studies indicate that inheritance of these two traits is independent (2), and this has led to newer variety releases with both a lower fall dormancy and improved winter hardiness. Genotypes with intermediate fall dormancy had relatively low injury compared with Vernal, a fall dormant cultivar (7). Ventroni et al (20) indicated that cutting frequency and fall dormancy of alfalfa are critical factors influencing both productivity and persistence; however, fall dormancy is not as critical as cutting frequency.…”
Section: Introductionmentioning
confidence: 99%